DIAGNOSTIC ACCURACY OF RESISTIVE INDEX IN DIFFERENTIATING BENIGN AND MALIGNANT SOLID BREAST LESION COMPARED WITH HISTOPATHOLOGICAL DIAGNOSIS (Journal of Medical & Health Sciences Review, 2025)
Background: Distinguishing between benign and malignant breast lesions early is essential for guiding treatment and avoiding unnecessary procedures. Doppler ultrasound, particularly the use of resistive index (RI), has shown promise as a non-invasive method to assess vascular characteristics of solid breast masses. This study assessed how accurately RI can identify malignancy, using histopathology as the reference standard.Methods: We carried out a descriptive cross-sectional study at the Radiology Department, Dr. Ruth K.M. Pfau Civil Hospital Karachi, over a six-month period. We included 291 women aged 20 to 70 years with solid breast lesions detected on grayscale ultrasound. All participants underwent Doppler ultrasound, and we used an RI value of ≥ 0.7 to indicate malignancy. Final diagnoses were confirmed through histopathology. We calculated sensitivity, specificity, predictive values, and diagnostic accuracy.Results: Out of 291 patients, Doppler ultrasound classified 229 lesions as malignant and 62 as benign. Histopathology confirmed malignancy in 208 cases. The RI threshold of ≥ 0.7 yielded a sensitivity and negative predictive value of 100%, specificity of 74.6%, positive predictive value of 90.8%, and overall diagnostic accuracy of 92.7%.Conclusion: An RI cut-off of 0.7 on Doppler ultrasound reliably identified malignant breast lesions in this study. Incorporating RI measurement into routine ultrasound may improve diagnostic confidence, support clinical decision-making, and reduce unnecessary biopsies, particularly in low-resource settings.